A revision of the Costa Rican species of Stenoeurilla Brailovsky & Barrera (Hemiptera: Heteroptera: Coreidae: Stenoscelideini), with the description of two new species, new distributional records, synonymical note, and key to the known species - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2019)
The genus Stenoeurilla Brailovsky & Barrera (Coreidae) in Costa Rica is revised. Two new species, S. herediana, and S. mesoamericana, are described. New distributional records for S. hansoni are added. A key to the known species of the genus is included. Photographs of dorsal habitus, male genital capsule and parameres are provided as well as drawings of hind tibiae. Stenoscelidea prolixa Brailovsky 1983 is placed in synonymy under Stenoeurilla aenescens (Stål) 1870.